2006
DOI: 10.1007/s00401-006-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of capillary cerebral amyloid angiopathy in Alzheimer lesion development: a regional comparison

Abstract: Recent studies have observed beta-amyloid-positive capillaries in lesion-prone regions of Alzheimer's disease (AD) brains. It is possible that there is a pathogenic link between neurofibrillary tangles (NFTs) and/or senile plaques (SPs) and altered capillary structure/function. In this study, we examined and compared brain tissue from a frequently observed NFT abundant area, the superior temporal cortex (ST), and a comparatively much NFT sparser area, the calcarine cortex (COC), in ten AD and ten normal adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…As well as being a core neuropathological finding in AD, neurofibrillary tangles have been demonstrated in association with CAA in patients with AD (Jeynes and Provias, 2006), and tau deposits (neurofibrillary tangles and pretangles) have been described in Aβ-related angiitis, an inflammatory form of CAA (Kurian et al, 2012). One study reviewing perivascular hyperphosphorylated tau in patients with AD found higher levels surrounding the CAA affected vessels than the unaffected ones (Williams et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As well as being a core neuropathological finding in AD, neurofibrillary tangles have been demonstrated in association with CAA in patients with AD (Jeynes and Provias, 2006), and tau deposits (neurofibrillary tangles and pretangles) have been described in Aβ-related angiitis, an inflammatory form of CAA (Kurian et al, 2012). One study reviewing perivascular hyperphosphorylated tau in patients with AD found higher levels surrounding the CAA affected vessels than the unaffected ones (Williams et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral amyloid angiopathy (CAA) is considered an important contributor in the pathogenesis of AD (Jeynes and Provias, 2006;Weller et al, 2009;Dickstein et al, 2010). CAA results from the accumulation of Ab within the structure of cerebral vessels or in the perivascular spaces surrounding them.…”
Section: Hypothesis Regarding the Trans-bbb Transport Of Ab In The Pamentioning
confidence: 99%
“…CAA results from the accumulation of Ab within the structure of cerebral vessels or in the perivascular spaces surrounding them. The result is therefore an accumulation of Ab in locations that transport it either into or out of the brain parenchyma or in the spaces whose function is to drain Ab into the venous or CSF compartments (Jeynes and Provias, 2006). In particular, capillary CAA (CAA-1) has been considered an important factor in the pathogenesis of sporadic AD.…”
Section: Hypothesis Regarding the Trans-bbb Transport Of Ab In The Pamentioning
confidence: 99%
See 2 more Smart Citations